2006
DOI: 10.1890/0012-9658(2006)87[2992:pfqdtw]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton Food Quality Determines Time Windows for Successful Zooplankton Reproductive Pulses

Abstract: Recruitment success at the early life stages is a critical process for zooplankton demography. Copepods often dominate the zooplankton in marine coastal zones and are prey of the majority of fish larvae. Hypotheses interpreting variations of copepod recruitment are based on the concepts of "naupliar predation," "nutritional deficiency," and "toxic effect" of diatom diets. Contradictory laboratory and field studies have reached opposite conclusions on the effects of diatoms on copepod reproductive success, blur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
100
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(110 citation statements)
references
References 26 publications
8
100
1
1
Order By: Relevance
“…Since survival in the plankton influences the arrival of recruits to adult populations, there is great interest in furthering our understanding of the physiology and ecology of early life history stages to improve management and conservation programs (Rumrill 1990, Morgan 1995. Factors such as temperature, food availability and quality, and predation can largely affect development and survival of larvae, their dispersal from the population of origin, and their chances of successfully completing metamorphosis after returning to shore (Thorson 1950, Pechenik 1987, Morgan 1995, Epifanio & Garvine 2001, Vargas et al 2006a,b, Emlet & Sadro 2006, O'Connor et al 2007). Sea temperature is probably the most important of these factors, as it influences all physiological and ecological processes of aquatic invertebrates and their life stages (Blaxter 1991, Somero 2002, O'Connor et al 2007, Pörtner & Farrell 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Since survival in the plankton influences the arrival of recruits to adult populations, there is great interest in furthering our understanding of the physiology and ecology of early life history stages to improve management and conservation programs (Rumrill 1990, Morgan 1995. Factors such as temperature, food availability and quality, and predation can largely affect development and survival of larvae, their dispersal from the population of origin, and their chances of successfully completing metamorphosis after returning to shore (Thorson 1950, Pechenik 1987, Morgan 1995, Epifanio & Garvine 2001, Vargas et al 2006a,b, Emlet & Sadro 2006, O'Connor et al 2007). Sea temperature is probably the most important of these factors, as it influences all physiological and ecological processes of aquatic invertebrates and their life stages (Blaxter 1991, Somero 2002, O'Connor et al 2007, Pörtner & Farrell 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Small copepods in the upwelling zone are mainly omnivorous, although as stated above, they can switch their diet to diatoms when the latter are abundant (Kleppel, 1993;Vargas et al, 2006), whereas large calanoid copepods prefer a more herbivore diet (diatoms) . Therefore, phytoplankton C can efficiently be transferred via grazing in highly productive upwelling systems, when small copepods are dominant, as in the coastal upwelling zone off Chile.…”
Section: Discussionmentioning
confidence: 91%
“…This analysis also showed that seasonal effects are important to determine grazing impact. Such seasonal variation takes place after shifts of copepod feeding to a more heterotrophic diet during conditions of low Chl-a (Vargas et al, 2006). Thus, transfer of phytoplankton through the pelagic food web via copepod grazing is not only more efficient during low Chl-a (autumn-winter), but it can also transfer more C through a heterotrophic pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations